[F-18]FDG imaging of head and neck tumors: Comparison of hybrid PET, dedicated PET and CT - Dresel, S.; Schwenzer, K.; Brinkbäumer, K.; Schmid, R.; Szeimies, U.; Pöpperl, G.; Hahn, K. (Nuklearmedizin - NuclearMedicine, 2001)
Aim: Aim of the study was to evaluate [F-18] FDG imaging of head and neck tumors using a Hybrid-PET device of the 2nd or 3rd generation. Examinations were compared to dedicated PET and Spiral-CT. Methods: 54 patients suffering from head and neck tumors were examined using dedicated PET and Hybrid-PET after injection of 185-350 MBq [F-18] FDG. Examinations were carried out on the dedicated PET first followed by a scan on the Hybrid-PET. Dedicated PET was acquired in 3D mode, Hybrid-PET was performed in list mode using an axial filter. Reconstruction of data was performed itera-tively on both, dedicated PET and Hybrid-PET. All patients received a CT scan in multislice technique. All finding have been verified by the goldstandard histology or in case of negative histology by follow up. Results: Using dedicated PET the primary or recurrent lesion was correctly diagnosed in 47/48 patients, using Hybrid-PET in 46/ 48 patients and using CT in 25/48 patients. Metastatic disease in cervical lymph nodes was diagnosed in 17/ 18 patients with dedicated PET, in 16/18 patients with Hybrid-PET and in 15/18 with CT. False positive results with regard to lymph node metastasis were seen with one patient for dedicated PET and Hybrid-PET, respectively, and with 18 patients for CT. In a total of 11 patients unknown metastastic lesions were seen with dedicated PET and with Hybrid-PET elsewhere in the body. Additional malignant disease other than the head and neck tumor was found in 4 patients. Conclusion: Using Hybrid-PET for [F-18] FDG imaging reveals a loss of sensitivity and specificity of about 1-5% as compared to dedicated PET in head and neck tumors. [F-18] FDG PET with both, dedicated PET and Hybrid-PET is superior to CT in the diagnosis of primary or recurrent lesions as well as in the assessment of lymph node involvement.
Keywords: Hybrid-PET; dedicated PET; [F-18] FDG; coincidence imaging; head and neck tumors